Analisis Penggunaan Eufemisme Dalam Pembuatan Berita Online Di Medialokal.co Edisi November 2022 - Sartika Sartika (Communiverse : Jurnal Ilmu Komunikasi, 2023)
The use of news language style is one of the characteristics in the world of journalism, one of which is the use of euphemisms. The use of euphemisms aims to make it easier for journalists to explain news content, in addition to refine the grammar of the news but also help the style of writing the news to make it more attractive to readers. This research method uses a descriptive qualitative approach, the data used in this study are in the form of words and sentences that contain euphemisms. The data obtained using the data card technique is read and recorded. The discussion of news focuses on one of the online news stories in the November 2022 edition of Medialokal.Co where the discussion of euphemisms is based on its form, namely the use of abbreviations, borrowed words, foreign words, metaphors and periphrasis.